Plant biodiversity patterns along a climatic gradient and across protected areas in West Africa. (6th April 2018) - Da, Sié Sylvestre; García Márquez, Jaime Ricardo; Sommer, Jan Henning; Thiombiano, Adjima; Zizka, Georg; Dressler, Stefan; Schmidt, Marco; Chatelain, Cyrille; Barthlott, Wilhelm
Abstract: Knowledge of spatial patterns of biological diversity is fundamental for ecological and biogeographical analyses and for priority setting in nature conservation, particularly in West Africa where the existing high biodiversity is increasingly threatened by human activities. The maximum entropy approach was used to model the geographic distribution of 3, 393 vascular plant species at a spatial resolution of 0.0833°. Species richness decreases along temperature and precipitation gradients with high species numbers in the south and lower numbers towards the north of the transect. All centres of plant species diversity are confined to humid areas in concordance with the high positive correlation between species richness and rainfall which appears to be the most important delimiter for the distribution ranges of many species in the area. The effectiveness of the existing protected areas at regional and national levels is investigated based on the proportion of species covered. Considering the whole study area, 95% of all species are covered by protected areas according to their distribution ranges. However, the proportion of species covered is considerably lower for some countries such as Benin and Togo. Our results could provide guidance for essential land use management interventions to decision‐makers and conservationists in the region.